Correlation of serum estradiol level on the day of ovulation trigger with the reproductive outcome of intracytoplasmic sperm injection - N Siddhartha; N Sanjeeva Reddy; Monna Pandurangi; M Tamizharasi; V Radha; K Kanimozhi (Wolters Kluwer Medknow Publications, 2016)
BACKGROUND: Serum estradiol (E2) levels are measured in in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI), to assess the ovarian response and to predict ovarian hyperstimulation syndrome. The impact of peak E2levels on IVF-ICSI outcome was found to be inconsistent in the previous studies. AIM: To evaluate the impact of the serum E2levels on the day of ovulation trigger with the reproductive outcome of ICSI. SETTINGS AND DESIGN: Retrospective observational study. ART Center, at a Tertiary Care University Teaching Hospital. SUBJECTS AND METHODS: Eighty-nine infertile women, who underwent ICSI with fresh embryo transfer over a period of 3 years, were included in the study. The study subjects were grouped based on the serum E2level on the day of ovulation trigger:- Group I - <1000 pg/ml, Group II - 1000-2000 pg/ml, Group III - 2000.1-3000 pg/ml, Group IV - 3000.1-4000 pg/ml, and Group V >4000 pg/ml. The baseline characteristics and controlled ovarian hyperstimulation (COH) outcome were compared among the study groups. STATISTICAL ANALYSIS USED: Chi-square test, Student's t-test, ANOVA, and logistic regression analysis. RESULTS: The study groups were comparable with regard to age, body mass index, ovarian reserve. Group V had significantly higher number of oocytes retrieved than I and II (18.90 vs. 11.36 and 11.33; P = 0.009). Group IV showed significantly higher fertilization rate than I, III, and V; (92.23 vs. 77.43, 75.52, 75.73; P = 0.028). There were no significant differences in the implantation rates (P = 0.368) and pregnancy rates (P = 0.368). CONCLUSION: Higher E2levels on the day of ovulation trigger would predict increased oocyte yield after COH. E2levels in the range of 3000-4000 pg/ml would probably predict increased fertilization and pregnancies in ICSI cycles.